An immodest demand: Valerie Solanas and SCUM Manifesto - Gibbs, Autumn (My University, 2019)
This presentation explores the "outlaw text" status of SCUM Manifesto, written in 1967 by Valerie Solanas, through its lack of impact upon the culture in the time it was published and now. Solanas and her manifesto have largely been left behind in the turbulent wake of second-wave feminism. The accompanying paper, written for one of the inaugural classes of Gender Studies 219, argues for increased visibility and analysis of the manifesto in feminism, academia, and popular culture.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: SCUM Manifesto; Valerie Solanas